Design of an in vitro biocatalytic cascade for the manufacture of islatravir - Huffman, Mark A; Fryszkowska, Anna; Alvizo, Oscar; Borra-Garske, Margie; Campos, Kevin R; Canada, Keith A; Devine, Paul N; Duan, Da; Forstater, Jacob H; Grosser, Shane T; Halsey, Holst M; Hughes, Gregory J; et al. (Science (American Association for the Advancement of Science), 2019)
Enzyme-catalyzed reactions have begun to transform pharmaceutical manufacturing, offering levels of selectivity and tunability that can dramatically improve chemical synthesis. Combining enzymatic reactions into multistep biocatalytic cascades brings additional benefits. Cascades avoid the waste generated by purification of intermediates. They also allow reactions to be linked together to overcome an unfavorable equilibrium or avoid the accumulation of unstable or inhibitory intermediates. We report an in vitro biocatalytic cascade synthesis of the investigational HIV treatment islatravir. Five enzymes were engineered through directed evolution to act on non-natural substrates. These were combined with four auxiliary enzymes to construct islatravir from simple building blocks in a three-step biocatalytic cascade. The overall synthesis requires fewer than half the number of steps of the previously reported routes.